Field and laboratory methods for grassland and animal production research - Jones, R. M. [ (Richard M.)]; Mannetje, L. 't (Cabi Ser, 2000)
This book brings together a range of methods used to study grasslands (both temperate and tropical) and ruminant performance, including: grassland vegetation and its measurement; pattern analysis in grassland and animal production systems; modelling pasure and animal production; measuring botanical composition of grasslands; measuring sward structure; plant population dynamics in grasslands; measuring biomass of grassland vegetation; evaluation of species and cultivars; remote sensing in vegetation and animal studies; assessing rangeland condition and trend; measuring chemical composition and nutritive value in forages; measuring physical, chemical and biological soil parameters in grasslands; measuring and monitoring nitrogen and phosphorus flows and losses in grassland systems; designing animal production studies; measuring animal performance; and development-oriented socioeconomic methods in grassland and animal production research. The book is primarily aimed at postgraduate students and researchers in these fields